STRATEGI PENGENTASAN KEMISKINAN DI ERA NEW NORMAL PRESPEKTIF AL-QUR'AN - Reni SE., MM (Universitas Sang Bumi Ruwa Jurai, 2022)
Abstract Poverty has been a problem for Muslims from ancient times to the present, inseparable from the conditions during the COVID-19 pandemic to the new normal as it is today. This study aims to describe strategies for poverty alleviation based on the Qur'an in the new normal era. This study uses a qualitative approach with a literature review with the method of interpreting the Qur'an about poverty and explaining how poverty alleviation is carried out, followed by an analysis of the alleviation strategy recommended in the Qur'an. The results of the study show that the Qur'an has a strategy in alleviating poverty, including the case of poverty in Indonesia in the new normal era, which will be a solution to the problem of poverty when applied properly and correctly, but in reality, Muslims, especially in Indonesia, are still accustomed to the habit of being lazy to move, lazy to work, to be complacent with other people's gifts that make them feel they don't need to work and try, pioneered by conditions that require people to stay at home with the implementation of WFH because Covid-19 is increasingly making people complacent with the habit of staying at home so that this causes a high unemployment rate which leads to an increase in the number of poverty. Keywords: Al-Qur'an, Poverty, New Normal